2019
DOI: 10.1371/journal.pone.0219985
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro media perfusion model of Leishmania major macrophage infection

Abstract: Background In vitro assays are widely used in studies on pathogen infectivity, immune responses, drug and vaccine discovery. However, most in vitro assays display significant differences to the in vivo situation and limited predictive properties. We applied medium perfusion methods to mimic interstitial fluid flow to establish a novel infection model of Leishmania parasites. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The activities of amphotericin B ( Figure 1 a), miltefosine ( Figure 1 b), paromomycin sulphate ( Figure 1 c) and sodium stibogluconate ( Figure 1 d) in the PEM– L. major amastigote model were determined at three different culture media flow rates, (i) static (0 m/s), (ii) low flow (1.45 × 10 −9 m/s; cells placed at bottom of well) and (iii) high flow (1.23 × 10 −7 m/s; cells placed on top of inserts) [ 42 ]. EC 50 and all measurable EC 90 values were altered by varying amounts as the speed of media perfusion was increased ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The activities of amphotericin B ( Figure 1 a), miltefosine ( Figure 1 b), paromomycin sulphate ( Figure 1 c) and sodium stibogluconate ( Figure 1 d) in the PEM– L. major amastigote model were determined at three different culture media flow rates, (i) static (0 m/s), (ii) low flow (1.45 × 10 −9 m/s; cells placed at bottom of well) and (iii) high flow (1.23 × 10 −7 m/s; cells placed on top of inserts) [ 42 ]. EC 50 and all measurable EC 90 values were altered by varying amounts as the speed of media perfusion was increased ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of perfusion of the culture medium on the infection levels of Leishmania was investigated using the QV900 media perfusion system (Kirkstall LTD, York, UK) developed and detailed in elsewhere [ 42 ]. The method for the static infection of PEMs seeded on 12 mm glass cover slips and their transfer to the QV900 is also described in O’Keeffe et al [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After each time point, the slides were examined as described above for the assay of chitosan activity against intracellular amastigotes of L. major and L. mexicana. The inhibition activity of the uptake (phagocytosis or pinocytosis) of the two inhibitors was evaluated on a fluorescence plate reader using fluorescent latex beads and pHrodo red dextran (72). We showed that cytochalasin caused 94 and 84% inhibition of phagocytosis of fluorescent latex beads (Sigma-Aldrich, UK) after 4 h and 24 h, respectively, and dynasore caused 95 and 90% inhibition of pinocytosis of pHrodo red dextran (M w ϭ 10,000; Thermo Fisher, UK) after 4 h and 24 h, respectively ( Table S6 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%